2022
DOI: 10.3390/gels8030147
|View full text |Cite
|
Sign up to set email alerts
|

Study of Several Alginate-Based Hydrogels for In Vitro 3D Cell Cultures

Abstract: Hydrogel, a special system of polymer solutions, can be obtained through the physical/chemical/enzymic crosslinking of polymer chains in a water-based dispersion medium. Different compositions and crosslinking methods endow hydrogel with diverse physicochemical properties. Those hydrogels with suitable physicochemical properties hold manifold functions in biomedical fields, such as cell transplantation, tissue engineering, organ manufacturing, drug releasing and pathological model analysis. In this study, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…It was shown that this thermosensitive hydrogel can be used as a three-dimensional platform with high biocompatibility and easy functionalization, and has great potential in the biomedical field. Similarly, Jiao et al [ 111 ] prepared sodium alginate-based composite hydrogels with good cell compatibility, which can be used for three-dimensional cell culture in vitro. Moreover, Nguyen et al [ 112 ] developed a co-culture system of ECM degradation products and MSCs with macrophages.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…It was shown that this thermosensitive hydrogel can be used as a three-dimensional platform with high biocompatibility and easy functionalization, and has great potential in the biomedical field. Similarly, Jiao et al [ 111 ] prepared sodium alginate-based composite hydrogels with good cell compatibility, which can be used for three-dimensional cell culture in vitro. Moreover, Nguyen et al [ 112 ] developed a co-culture system of ECM degradation products and MSCs with macrophages.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Thermo-responsive hydrogels are supramolecular hydrogels that undergo a gelation process via hydrophobic interaction. Hydrogels can undergo sol–gel phase transition because they consist of amphiphilic polymers with hydrophilic and hydrophobic components [ 73 ]. Hydrogels can undergo a gelation process from room temperature to body temperature (range of 25–37 °C), which is beneficial for their application in tissue engineering [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alginate offers a fantastic toolset for design and optimisation, even though one system is likely to fit only some research or cell types [120]. The hydrogels used for in vitro 3D cell culturing have specific physicochemical characteristics, such as hardness, water holding capacity (WHC), swelling-erosion ratio, and swelling rate, to mirror the natural extracellular matrices (ECMs) found in living things [122].…”
Section: Cell Immobilisationmentioning
confidence: 99%